2019
DOI: 10.1097/anc.0000000000000642
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Distress in the Neonatal Intensive Care Unit

Abstract: Background: The neonatal intensive care unit (NICU) can cause significant psychological distress in a mother. There is no common definition of maternal distress in the NICU currently in use. Purpose: To develop a clear conceptual understanding of maternal distress in the NICU using conceptual definitions and empirical findings. Methods/Search Strategy: A literature search was conducted using EBSCOhost, MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…In this study, women with poor support from their spouses were more likely to suffer from PTSD or PTSD Profile (28.6%) compared to the women with good support from their spouse (9.8%), the second groupseems to manage better the consequences of traumatic CS.A lot of studies reveal the relationship between social support and good health and suggest that the psychical reaction to stress is under the influence on the level of family and spouse support [49]. Focusing specifically on this, some studies agree with the present study and confirm the effective role ofpartners'supportto reduce the incidence of postnatal PTSD and PTSD Profile [15,44].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, women with poor support from their spouses were more likely to suffer from PTSD or PTSD Profile (28.6%) compared to the women with good support from their spouse (9.8%), the second groupseems to manage better the consequences of traumatic CS.A lot of studies reveal the relationship between social support and good health and suggest that the psychical reaction to stress is under the influence on the level of family and spouse support [49]. Focusing specifically on this, some studies agree with the present study and confirm the effective role ofpartners'supportto reduce the incidence of postnatal PTSD and PTSD Profile [15,44].…”
Section: Discussionsupporting
confidence: 85%
“…Another very important factor predicting PTSD-ACwhich is associated with preterm labor and complications during pregnancy is the inclusion of the infant in the NICU. It is known that maternal distress after the inclusion of the infant in the NICUconsists of a complication of anxiety, depressive and PTSD symptoms and is associated negatively with maternal-infant attachment [44,45]. In our study, inclusion inthe NICU is related to 30.2% of EMCS and 11.3% of ELCS and includes preterm and full-term infants.…”
Section: Discussionmentioning
confidence: 64%
“…For parents of very preterm infants, the alteration in their parental role is recognized as the most important stressor [ 5 , 6 ]. This altered role may contribute to an increased risk of feeling depressed or anxious, compared with parents of healthy full-term infants [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This altered role may contribute to an increased risk of feeling depressed or anxious, compared with parents of healthy full-term infants [ 7 ]. Parents may feel disrupted in their ability to care for the infant, because of illness severity, medical procedures they cannot perform, and limited access [ 5 , 6 ]. Whether a relationship exists between the stress experienced by an infant and the anxiety subsequently experienced by its parents has not been demonstrated before, even though this seems obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, more than a third of participants screened positively for post-traumatic stress. Previous work has identified that maternal distress is often marked by post-traumatic stress, depression and anxiety and prevalent in mothers whose infants have been hospitalized in the NICU [38]. Understanding both the mother's personal history of mental health disorders, social complexity and support systems are important when interpreting depression and post-traumatic stress screening [39].…”
Section: Discussionmentioning
confidence: 99%